The dilemma of indigenous researchers: A review to qualitative and quantitative research methods with reference to children with special educational needs - Abdelbasit Gadour; Samia Amniana (Britain International for Academic Research (BIAR) Publisher, 2014)
There is a growing concern among indigenous researchers with the reliability of the methods used to get insights into the phenomena of concern. This study explores the techniques/methods used to collect information on children’s special educational needs within Libyan mainstream schools. This is with the aim to underline the advantages and disadvantages of each method used within unfamiliar context to where they initially created. Moreover issues relating to validity and reliability, sampling and generalisability are considered here and attention is drawn to the sample and population selected.